Palliative sedation : Development and consensus of a German language documentation template - Klein, Carsten; Wittmann, C.; Wendt, K. N.; Ostgathe, Christoph; Stiel, S. (Anaesthesist, 2018)
BACKGROUND: Palliative sedation (PS) serves as a therapeutic option in cases of otherwise intractable suffering. As the use of sedative and hypnotic medication in many diverse situations is a core competency of anesthesiology, anesthesiologists are confronted with questions of sedative therapy at the end of life in institutions for specialized palliative care, in intensive care units and intermediate care wards. In recent years a number of guidelines have been published internationally but so far no official guidelines exist in Germany. The most recognized document is the European Association for Palliative Care (EAPC) framework on PS. This project aims to develop a German language template for the preparation, application, documentation and evaluation of PS according to the current frameworks, especially the EAPC framework on PS. METHODS: A first draft of the template was generated by the project team using the EAPC framework and individual templates of various institutions, which had been collected during a previous project. Professionals (n = 136) from inpatient and outpatient specialist palliative and hospice care were invited to assess all items of the draft regarding "relevance", "wording" and "feasibility" in an online Delphi survey (Unipark®, Questback, Cologne, Germany). After the second Delphi round an expert panel was asked to reflect the results and generate a final draft. Approval was granted if acceptance exceeded 75% of participants. RESULTS: The 3 rounds of the Delphi process were completed by 64, 46 and 41 participants, respectively. The Delphi process as well as the expert panel led to significant changes of the template. The indications for PS had to be clarified. The significance of documentation of vital parameters, such as oxygen saturation, blood pressure or respiratory rate during PS was intensively discussed. In many teams, predominantly hospice or outpatient palliative care teams, it seems to be difficult to measure these parameters or it is regarded as inappropriate in a palliative care setting. In contrast, the EAPC framework recommends monitoring of vital parameters in cases of intermittent or respite sedation. Finally, a solution was found to support documentation of additional data without the explicit mentioning of specific parameters. After the third Delphi round, all 16 items of the documentation template reached consensus with respect to relevance (82.9-100%), clarity of wording (80.5-100%), and feasibility in practice (78-100%). CONCLUSION: This article provides an empirically based, multiprofessional consented documentation template for PS. Core elements of the documentation of PS are the indications and the decision process towards PS. During the treatment, at least the level of sedation and the symptom burden have to be recorded. The documentation of vital signs during PS remains a highly disputed topic. The presented data suggest that especially in outpatient settings and in hospices measuring and documentation of vital parameters is uncommon and therefore is often regarded as not feasible. This template can help to support the medically and ethically sound use of PS and facilitate research. The template can be accessed at http://www.palliativmedizin.uk-erlangen.de/forschung/downloads/ .
EVALuna2:34947